Tipos de personalidad y rendimiento académico en matemáticas con estudiantes de primero de bachillerato de la Unidad Educativa Comunitaria Intercultural Bilingüe “Hualcopo Duchicela - Mullo Naula, Mery Anabella (2025)
The purpose of this research was to analyze the relationship between personality types and academic performance in Mathematics among first-year high school students at the Hualcopo Duchicela Intercultural Bilingual Community Educational Unit. The research used a quantitative, non-experimental design with a correlational research level, and was a fundamental field study. A sample of 65 first-year high school students from the institution under analysis was established using non-probability convenience sampling. A questionnaire consisting of 50 questions on a Likert scale, divided into two dimensions, was designed to collect data. Same that helped to collect information on extroverted and introverted personality types, as well as data on the academic performance of students, on the other hand, the relationship between personality types and the academic performance of students was determined, finally, pedagogical strategies that can facilitate effective and personalized learning were proposed, this questionnaire was validated by experts from the National University of Chimborazo. Through the application of Pearson's Chi square and Cramer's V coefficient, the results of the research revealed that the introverted spectrum has no relationship with the academic performance of first-year high school students, moreover, the extroverted spectrum did present a relationship with the academic performance of first-year high school students belonging to the Bilingual Intercultural Community Educational Unit "Hualcopo Duchicela"; therefore, it is recommended that teachers implement varied pedagogical strategies considering the different types of personalities of the students, in order to promote a more equitable education adapted to their individual needs.